Pengaruh ROE, EPS, dan Reputasi Underwriter terhadap Tingkat Underpricing Stock pada Perusahaan IPO di ISSI - Rachmi Amelia; Hasbi Assidiki Mauluddi; Radia Purbayati (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Companies need additional capital, one of which is from external companies by conducting initial public offerings on the capital market, but companies often experience underpricing in the secondary market. This study aims to develop findings regarding the phenomenon of underpricing in IPO companies and to determine the effect of return on equity (ROE), earnings per share (EPS), and underwriter's reputation on the level of underpricing. The population in this study are companies that have conducted an Initial Public Offering (IPO) that are registered on the Indonesian Sharia Stock Index (ISSI) and are not delisted on the Sharia Securities List (DES) in the period 2019 to 2022. The research sample was taken using a purposive sampling method to obtain a sample of 104 companies. Data analysis used multiple linear regression analysis with the SPSS 22 program. The results found that the average level of underpricing was 31,19%. Simultaneously the variables ROE, EPS, and underwriter's reputation have a significant effect on the level of underpricing. While partially, it shows that ROE has a negative and significant effect on the level of underpricing, the reputation of underwriters has a positive and significant effect on the level of underpricing, and earnings per share does not affect the level of underpricing. Keywords: Underpricing, Initial Public Offering, Return on Equity (ROE), Earning per Share (EPS), Reputasi Underwriter